Social Media Paradoxes: Power, Submission and Awareness. A Netnographic Analysis of #Metoo. - Castillo-de-Mesa, Joaquín; Marcuello Servós, Chaime (My University, 2019)
This paper aims to describe some paradoxes of social media using Sociocybernetics. We will develop a netnographic analysis of #Metoo as case study to discuss three controversial key points: power, submission and awareness. Millions of people around the world embrace Internet. The information and communication technologies (ICTs) have transformed the traditional way of life. Now it is evidence. Our digital societies are mediated by software and hardware. This requires a theoretical framework to consider the effects of the "Internetization" and "digitalization' of our lives and especially, its effects in the emergence of social movements. Online social networks have become a parallel universe of socialization from which interactive dynamics are generated until recently unknown. From this framework of online communication, different social movements have reached a greater diffusion. One of them is #Metoo. Here we analyse longitudinally, from March 2018 to March 2019, the social movement #Me too on Twitter. Based on the network analysis methodology, the characteristics of the observed online social structure are analysed. Netnography findings serve to show a high level of emotion in the way of interacting and a significant pattern of polarization in the conversations about the movement. In addition, this netnographic characterization maps the paradoxes of power relations, the forms of submission and the levels of consciousness that are handled in social networks such as Twitter.
Keywords: Redes sociales en Internet - México; Movimientos sociales; Power; Submission; Awareness